STUDY OF PUMPING UNIT OPERATING PARAMETERS IN ORDER TO REDUCE ENERGY COSTS UNDER OPERATING CONDITIONS - Qurbonov O. M.; Asatova S. S. (American Journals Publishing, 2024)
The overall energy consumption depends to a large extent on the pumping equipment. The efficiency of a pumping station is often lower than the efficiency of the individual pumps installed in it. The reason for the low energy efficiency lies in the mismatch between the operating characteristics of the equipment as well as its improper management. To improve the efficiency of pumping plants it is necessary to reduce the cost of operating the pumping equipment, increase its reliability and longevity, this requires the correct selection of the operating modes of the plant and the parameters of the external network.Optimization of the operating modes of pumping units is possible through real measurements of the operating parameters of specific brands with the use of control and measuring equipment directly at the sites during operation.In the article the results of research of mode parameters of pumping installations and results of experimental works on determination of optimum operating modes of centrifugal pump of WCP 25-60G brand are given.
Keywords: Centrifugal pumps, economical operation, energy efficiency improvement, optimal operation mode of pumping equipment, head and delivery, pressure and flow characteristics of the pump, pressure and flow rate of liquid.